2019
DOI: 10.1111/sjtg.12300
|View full text |Cite
|
Sign up to set email alerts
|

Exploring livelihood transitions in the Mekong delta

Abstract: Important environmental and economic changes are transforming livelihoods in coastal communes throughout the Mekong delta. In the process, the historical reliance on rice farming and fishing has become less viable and sustainable, forcing households to construct more complex livelihood strategies. To document these livelihood transformations, we have analyzed primary survey data from 346 households across eight coastal communes in Ca Mau Province, located in the southern tip of Vietnam's Mekong delta. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…On the other hand, we found that the majority of the studies (61%) still established a direct relationship between environmental or climate risk and human mobility. Only four studies (14%) (Betcherman et al, 2021;Khong et al, 2020;Smajgl et al, 2015;Zickgraf, 2019) explicitly state that they could not find a direct relationship between environmental or climate change and human mobility.…”
Section: Academic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we found that the majority of the studies (61%) still established a direct relationship between environmental or climate risk and human mobility. Only four studies (14%) (Betcherman et al, 2021;Khong et al, 2020;Smajgl et al, 2015;Zickgraf, 2019) explicitly state that they could not find a direct relationship between environmental or climate change and human mobility.…”
Section: Academic Studiesmentioning
confidence: 99%
“…Further, environmental processes occurring at different scalar levels or in other places can affect different groups' livelihoods. As an example, dam building in the Mekong serves upstream governments and residents (Marks & Zhang, 2019), yet potentially threatens the livelihoods of small-holder rice/aquaculture farmers in the MKD downstream (Betcherman et al, 2021).…”
Section: Towards a Political Ecology Framework On Human Mobility In R...mentioning
confidence: 99%
“…Furthermore, adaptation trajectories are embedded within social and environmental contexts across scales and places: processes occurring at different scalar levels or other places can affect these groups' potential pathways. As an example, dam building in the Mekongwhich provides electricity for residents upstream and income to their governments-will likely make it more difficult for powerless aquaculture farmers downstream to adapt and maintain their livelihoods (Betcherman et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Betcherman et al . (2021, this issue) use a household survey, focus group discussions and interviews to investigate livelihood transitions among coastal households in the Mekong Delta between 2002 and 2012. They find that households respond to changing economic and environmental circumstances in pursuit of economic benefits and conclude that we may be experiencing a third agricultural transition characterized by a shift to diversified livelihood activities, in many cases away from fishing or aquaculture.…”
mentioning
confidence: 99%
“…Betcherman et al . (2021, this issue) likewise find that households in the Mekong Delta will continue to adapt their livelihoods in the light of locally changing environments—to some extent aggravated by anthropogenic influence—including ongoing saline intrusion, flooding events and sea level rise. Vicol and Pritchard (2021, this issue) contrast the Ayeyarwady Delta's biophysical environment, rich in alluvial soils and abundant water that provided the material foundation for the expansion of the rice frontier, with its present socio‐economic landscape, which they describe as wracked by poverty.…”
mentioning
confidence: 99%